Proton pump inhibitors: potential cost reductions by applying prescribing guidelines - Cahir Caitriona; Fahey Tom; Tilson Lesley; Teljeur Conor; Bennett Kathleen (BMC, 2012)
Abstract Background There are concerns that proton pump inhibitors (PPI) are being over prescribed in both primary and secondary care. This study aims to establish potential cost savings in a community drug scheme for a one year period according to published clinical and cost-effective guidelines for PPI prescribing. Methods Retrospective population-based cohort study in the Republic of Ireland using the Health Services Executive (HSE) Primary Care Reimbursement Services (PCRS) pharmacy claims database. The HSE-PCRS scheme is means tested and provides free health care including medications to approximately 30% of the Irish population. Prescription items are WHO ATC coded and details of every drug dispensed and claimants' demographic data are available. Potential cost savings (net ingredient cost) were estimated according to UK NICE clinical guidelines for all HSE-PCRS claimants on PPI therapy for ≥3 consecutive months starting in 2007 with a one year follow up (n=167,747). Five scenarios were evaluated; (i) change to PPI initiation (cheapest brand); and after 3 months (ii) therapeutic switching (cheaper brand/generic equivalent); (iii) dose reduction (maintenance therapy); (iv) therapeutic switching and dose reduction and (v) therapeutic substitution (H2 antagonist). Results Total net ingredient cost was €88,153,174 for claimants on PPI therapy during 2007. The estimated costing savings for each of the five scenarios in a one year period were: (i) €36,943,348 (42% reduction); (ii) €29,568,475 (34%); (iii) €21,289,322 (24%); (iv) €40,505,013 (46%); (v) €34,991,569 (40%). Conclusion There are opportunities for substantial cost savings in relation to PPI prescribing if implementation of clinical guidelines in terms of generic substitution and step-down therapy is implemented on a national basis.